Combination of superplasticizers with hydroxypropyl guar, effect on cement-paste properties. (10th August 2019) - Govin, Alexandre; Bartholin, Marie-Claude; Schmidt, Wolfram; Grosseau, Philippe
Highlights: A specific method is proposed for adsorption quantification of PCE combined with HPG. The adsorption of the HPG is decreased by the presence of PCE. The adsorption of only the lowest charged PCE is affected by the HPG. The change in adsorption modifies the yield stress and the viscosity of the pastes. Abstract: Viscosity-modifying agent (VMA) are used in several applications of concrete, such as underwater concrete, Self-Compacting Concrete (SCC) or Self-Levelling Underlayments (SLU) in order to improve the washout resistance and the stability. The study focuses on the modifications of cement pastes properties implied when a VMA (hydroxypropyl guars or HPG) and a superplasticizer are introduced together. For reaching this objective, two chemically different polycarboxylate-based superplasticizers (PCE) and two HPGs exhibiting different molar substitution ratios (MSHP ), were studied. A method, combining total organic carbon and size exclusion chromatography, was developed in order to quantify the adsorption of the both admixtures. The adsorption of HPGs appears being significantly lowered by the presence of PCE, while only the adsorption of the less charged PCE is slightly affected by the HPG. As consequence, strong modifications of the rheological properties of cement pastes were noticed when HPG and PCE are combined. The desorption of HPG leads to higher yield stress and residual viscosity than with PCE alone.